Evolution and synthesis of novel orally bioavailable inhibitors of PDE10A. Issue 9 (1st May 2015) - Burdi, Douglas F.; Campbell, John E.; Wang, Jun; Zhao, Sufang; Zhong, Hua; Wei, Jianfeng; Campbell, Una; Shao, Liming; Herman, Lee; Koch, Patrick; Jones, Philip G.; Hewitt, Michael C.
Graphical abstract: The evolution and synthesis of potent, orally bioavailable inhibitors of PDE10A is described. Abstract: The design and synthesis of highly potent, selective orally bioavailable inhibitors of PDE10A is reported. Starting with an active compound of modest potency from a small focused screen, we were able to evolve this series to a lead molecule with high potency and selectivity versus other PDEs using structure-based design. A systematic refinement of ADME properties during lead optimization led to a lead compound with good half-life that was brain penetrant. Compound39 was highly potent versus PDE10A (IC50 = 1.0 nM), demonstrated high selectivity (>1000-fold) against other PDEs and was efficacious when dosed orally in a rat model of psychosis, PCP-induced hyperlocomotion with an EC50 of 1 mg/kg.